Endometrial stromal sarcomas with BCOR internal tandem duplication and variant BCOR/BCORL1 rearrangements resemble high-grade endometrial stromal sarcomas with recurrent CDK4 pathway alterations and MDM2 amplifications - Kommoss, Felix; Chiang, Sarah; Köbel, Martin; Kölsche, Christian; Chang, Kenneth Tou-En; Irving, Julie A.; Dickson, Brendan; Thiryayi, Sakinah; Rouzbahman, Marjan; Rasty, Golnar; Deimling, Andreas von; Lee, Cheng-Han; et al. (The American journal of surgical pathology, 2022)
The distinction between low-grade and high-grade endometrial stromal sarcomas (LGESS, HGESS) is increasingly defined by genetics. Recently, variant genomic alterations involving BCOR or BCORL1 have been reported in endometrial stromal sarcoma (ESS), although it remains unclear whether these justify a diagnosis of LGESS or HGESS. In this study, we describe clinicopathologic and molecular features of ESS with such alterations to help clarify their classification in the spectrum of ESS. We collected a cohort of 13 ESS harboring variant alteration involving BCOR (6 with internal tandem duplication, 1 with EP300::BCOR fusion, 1 with BCOR::LPP fusion) and BCORL1 (4 with JAZF1::BCORL1 fusion, 1 with EPC1::BCORL1 fusion). The median patient age at primary diagnosis was 51 years (range: 18 to 70 y). Median tumor size at primary diagnosis was 9.3 cm (range: 4.5 to 21 cm), and extrauterine disease spread (stage IIIB-C) was present in 27%. The tumors were composed of round to spindled cells with cellularity and cytologic atypia ranging from mild to marked and a median mitotic count of 18/10 HPFs (range: 2 to 85/10 HPFs). At least focally myopermeative growth was noted in 8/8 assessable cases. Of 12 patients with follow-up data (median: 25 mo), 4 patients died of disease and 3 were alive with recurrent disease. Unsupervised hierarchical clustering of DNA methylation data together with a large cohort of uterine mesenchymal tumors that included YWHAE::NUTM2 and ZC3H7B::BCOR HGESS and molecularly confirmed LGESS revealed a common methylation signature for all ESS with variant BCOR and BCORL1 alterations and HGESS with YWHAE::NUTM2 and ZC3H7B::BCOR gene fusion. Copy number analysis revealed amplifications of CDK4 and MDM2, as well as homozygous deletions of CDKN2A/B and NF1 in a subset of tumors. Our results indicate that ESS with BCOR internal tandem duplication and variant BCOR and BCORL1 rearrangements clinically and molecularly resemble conventional HGESS.